Beta Karoten, Daun Kelor, Spektr PERBEDAAN KADAR BETA KAROTEN ANTARA DAUN KELOR SEGAR DAN KERING MENGGUNAKAN METODE SPEKTROFOTOMETRI UV-VIS - Nurul Hadiatun Hadiatun; Baiq Isti Hijriani; Siska Zafrida; Ainutajriani (Poltekkes Kemenkes Medan, 2023)
Moringa leaves are part of the moringa plants that contain nutrients. The chemical compounds contain in moringa leaves are very much, one of them is beta carotene. Beta carotene is a very potential source of vitamin A and has the highest vitamin A activity of all carotenoids. The purpose of this study was to determine beta carotene content in fresh and dry moringa leaves using UV-Vis spectrophotometry method. The population was the moringa leaves, sample was fresh and dry Moringa leaves. Method and analysis of this research was conducted by descriptive method. The results were 19,82?g/g beta carotene of fresh leaves, whereas in dry leaves was 187,45?g/g at 461,1nm wavelength by UV-Vis spectrophotometry. These were caused by various factors, such as; environment, temperature, and humidity. Drying process for dry leaves also affect the beta carotene content of the samples. The conclusion was beta carotene content of dry leaves higher (187.45 ?g/g) than fresh leaves (19.82 ?g/g). Suggestion of this research, it is necessary to measure Moringa oleifera leaves before drying process into oven, make the same sample with different method, or do research with different sample but using the same method